A Pilot Study of a Trauma‐Informed Yoga and Mindfulness Intervention With Young Women Incarcerated in the Juvenile Justice System. Issue 2 (5th October 2021) - Nicotera, Nicole; Viggiano, Erica
Abstract : This pilot study examined an 8‐week yoga‐mindfulness intervention with girls in the juvenile justice system. Pre‐ and posttest data were collected via the Mindful Awareness and Attention Scale for Adolescents (MAAS‐A). Paired t tests demonstrated a significant increase in mean MAAS‐A scores.